Implementasi Prinsip Pembiayaan Pada Lembaga Keuangan Syariah - Vani Hajari; Chuzaimah Batubara (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Islamic Financial Institutions (LKS) exist as an option and alternative to the needs of the community according to sharia and far from usury as it is in Islamic Financial Institutions (LKS). LKS comes with a concept and system that can meet the demands and needs of the community, with a profit and risk sharing system that prioritizes the principles of fairness and solidarity in doing business, both taking and taking risks. The basics in the LKS include the principle of saving or (al-wadi'ah), the principle of profit sharing including mudharabah and musyarakah, the principle of buying and selling which includes murabahah, salam and istishna, the principle of leasing (ijarah) and the principle of servitude. Including wakalah, kafalah, hawalah, rahn, qardh, sharf. The purpose of this article is to explain the implementation of financing principles in Islamic financial institutions. This study uses qualitative methods based on information gathering. The implementation of sharia principles in Islamic financial institutions is something that is very urgent and important to implement, which is the core of the operations of Islamic financial institutions. Fairness, Partnership, Transparency, Universal. Financing is one type of product and activity of Islamic banks in channeling funds to other parties whose operations are based on sharia principles.